2013
DOI: 10.1016/j.crohns.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mucosal expression in ulcerative colitis, the relationship between cytokine release and disease activity

Abstract: Our findings suggest that IL-8 is elevated and TGFβ is reduced in distal colitis. Lower concentration of IFNγ, IL-4 and IL-17A were also noted. TNFα levels were unchanged. These findings suggest that the inflammatory response in UC may predominantly involve IL-8 mediated neutrophil infiltration and failure of TGFβ mediated tissue healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
3
17
0
1
Order By: Relevance
“…Cytokine IL-8 is a neutrophil chemoattractant secreted by intestinal epithelial cells as a response to inflammatory stimuli, such as bacterial molecules (Lammers et al, 1994;Mitsuyama et al, 1994). Colonic IL-8 levels have been shown to correlate with the degree of intestinal inflammation and the number of neutrophils in the mucosa in UC and CD patients (Mitsuyama et al, 1994;Pearl et al, 2013). Undifferentiated HT-29 cells were used in the IL-8 assays due to the downregulation of IL-8 in LPS-induced differentiated HT-29 cells as well as due to the assay optimization in our previous studies using undifferentiated HT-29 cells (Böcker et al, 2000;Hiippala et al, 2016Hiippala et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine IL-8 is a neutrophil chemoattractant secreted by intestinal epithelial cells as a response to inflammatory stimuli, such as bacterial molecules (Lammers et al, 1994;Mitsuyama et al, 1994). Colonic IL-8 levels have been shown to correlate with the degree of intestinal inflammation and the number of neutrophils in the mucosa in UC and CD patients (Mitsuyama et al, 1994;Pearl et al, 2013). Undifferentiated HT-29 cells were used in the IL-8 assays due to the downregulation of IL-8 in LPS-induced differentiated HT-29 cells as well as due to the assay optimization in our previous studies using undifferentiated HT-29 cells (Böcker et al, 2000;Hiippala et al, 2016Hiippala et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is a type of inflammatory bowel disease (IBD) which is usually confined to the colon and rectum, with diffuse and superficial lesions of the mucosa [1]. Mucosal inflammation correlated with disease severity is UC characterised [2]. Rich evidences suggested that cytokines played an essential role in the mucosal inflammatory by promoting leukocyte migration to sites of inflammation and ultimately leading to tissue damage and destruction [3].…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 expression levels are high in the inflamed mucosa of patients with UC (17-19) and Pearl et al (12) reported that there was an association between the severity of inflammation and the mucosal concentration of IL-8. The present study showed that IL-8 expression levels were upregulated in the inflamed regions of the colon in patients with UC, and this effect was independent of patient background factors such as sex, location of lesions, type of disease, combinations of treatment, and presence/absence of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, there are several reports on the role of MUC2 and LYPD8 in UC; however, only two studies have examined the role of MUC2 and LYPD8 in the context of severity of inflammation and gene expression in UC (12,13). Furthermore, to the best of our knowledge, there are no studies comparing their gene expression in the lesioned and non-lesioned regions of the colon in patients with UC.…”
Section: Introductionmentioning
confidence: 98%